Financial Literacy, Inclusion, and Technology Adoption: Determinants of QRIS Utilization Among SMEs - Kadek Erma Damayanti; I Gusti Ayu Made Asri Dwija Putri (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
Quick Response Code Indonesian Standard (QRIS) is a digital payment system in Indonesia that utilizes QR codes to facilitate transactions through digital wallets and banking applications, enabling fast, secure, and efficient payments. This study aims to empirically examine the impact of Financial Literacy, Financial Inclusion, and Ease of Use on the decision to adopt QRIS among Small and Medium Enterprises (SMEs) in Denpasar. Data collection was conducted through both offline and online surveys using structured questionnaires distributed to micro, small, and medium enterprise (MSME) owners who actively use QRIS in their business transactions. A total of 100 responses were gathered and analyzed using SPSS. The findings reveal that Financial Literacy and Ease of Use significantly influence the decision to adopt QRIS, while Financial Inclusion does not have a significant effect. These results suggest that enhancing financial knowledge and ensuring the usability of digital payment systems are crucial factors in promoting QRIS adoption among SMEs.